A study on position of the state secretary in Selangor: the law and practice / Mazni Ibrahim, Nur Huda Mohamad and Siti Asmath Che Man - Ibrahim, Mazni; Mohamad, Nur Huda; Che Man, Siti Asmath (2011)
The topic on "A Study on Position of the State Secretary in Selangor: The Law and Practice'' was proposed following the incident in Selangor in December 2010 where there was a conflict between the appointment of the State Secretary by the Federal and the State. A State Secretary is the Head of the State Civil Servant which represents the civil servants of a state as a whole. Generally, the Public Services Commission has jurisdiction over the Federation, Malacca and Penang. The jurisdiction is extended to any state which has no State Services Commission. However, there seems to be an overlapping in terms of jurisdiction as highlighted in the incident that has happened in the state of Selangor on the appointment of a senior public officer, the State Secretary. This study contains a brief introduction on the principle of federalism as well as the key to the study as to the words "appropriate service Commission". The objective of the study is to analyse related procedures and provisions and, where possible related recommendations. The scope and limitation as well as the significance of the study are spelled out with the purpose of doing the study in relation to the appointment of a State Secretary. The literature review is the opinion of academicians and legal practitioners. Besides that, the proposal is also coded with a qualitative research and interview as the methodology for the study. We hope this study will be a guide for those who would like to understand the legal position of a public servant in theory and practical as well as the legal aspects and its implications on the above issue.